(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Malaria is one of the most lethal tropical illnesses known to man, and it’s becoming worse because to an increase in drug resistance in the malaria-causing protozoan to conventional treatments. There are many species of the protozoan falciparum which causes various types of malaria. Several, synthetic, semisynthetic & natural origin compounds having anti-malarial property has been commercialized. Some of them are as follows: chloroquine is a quinine derivative whereas artesunate having sesquiterpene lactone core is derived from artemisinin that is isolated from Artemisia annua L. Though the artemesinin based combination therapy (ACT) has showed excellent results however, the rising cases of drug resistance is now making the researchers to search for more novel therapies. In this review paper, the life cycle of a malarial protozoan, the current artemesinin combination therapy and the other phyto-molecules having anti-malarial activity has been briefed upon. One can believe that the discovery of novel phyto-molecules having would lead to a much safer, effective and cheaper mode of treatment of malaria.